Enhancement of tonic and phasic GABAergic currents following nitric oxide synthase inhibition in hippocampal CA1 pyramidal neurons. (17th March 2015) - Gasulla, Javier; Calvo, Daniel J.
Highlights: Tonic and phasic GABAA receptor activity was measured in hippocampal slices. Effects of nitric oxide depletion on GABAA receptor mediated responses were examined. Tonic and phasic GABAA receptor responses were potentiated after NOS inhibition. GABAA receptors in CA1 hippocampal neurons are modulated by basal NO levels. Abstract: Nitric oxide (NO) is involved in synaptic plasticity in the hippocampus through different presynaptic and postsynaptic mechanisms that include the modulation of the GABAergic neurotransmission. Inhibitory synapses on hippocampal pyramidal neurons are known to possess the molecular machinery for retrograde NO-signaling, but the modulation of GABAA Rs function by NO in these neurons and the mechanisms of action involved have not been fully characterized. Here we show that suppression of the endogenous NO generation by the nitric oxide synthase (NOS) inhibitor L-NAME produces significant and reversible increases in the magnitude of both tonic and phasic GABAergic currents in CA1 hippocampal pyramidal neurons. GABA-evoked chloride currents were measured in the presence or absence of L-NAME using whole-cell patch-clamp recordings in acute hippocampal slices from young adult mice. Enhancement of the tonic GABA responses induced by L-NAME was insensitive to TTX and decreased by co-incubation with the NO donor DEA/NO. Applications of DEA/NO alone did not produce significant effects on tonic GABA responses. L-NAME treatment also increased the amplitude of phasic GABAergic currents evoked by GABA-puffs. Our results indicate that the extent of tonic and phasic inhibition mediated by GABAA receptors in CA1 hippocampal pyramidal neurons is affected by endogenous NO production.